Natural Language Processing: Comprehensive Review - Vinothina, V (International Journal of Computer Sciences and Engineering, 2025)
The emerging and most popular processing technique of Natural Language Processing (NLP) deals with computational algorithms to analyze and process human language. It also represents human language. The application of NLP enabled system ranges from search engine to voice assistant, machine translation and dialogue generation. It is concerned with interaction between computers and natural language such as human language. High-revenue non NLP-domain such as finance, government surveillance or marketing is the areas benefited from NLP. The main objective of this paper to review state-of-the art of NLP, its benefits and various processes in NLP enable the systems to deal with real-time data.